Implementation of Development Management Local Content Curriculum in Modern Islamic Boarding Schools Al-Azhary Lesmana - Nurkholis Nurkholis; Saumi Setyaningrum; Abdul Razak Abdulroya Panaemalae (The Magister of Islamic Education Study Program of Postgraduate IAIN Pontianak, 2022)
The purpose of this research is to determine the development of the local content curriculum in the modern Islamic boarding school Al-Azhary Lesmana Ajibarang Banyumas. This research is qualitative research using gap evaluation (DEM). This research was conducted in early 2022. Data collection used observation, interviews, and documentation studies. Data were analyzed descriptively and qualitatively. Evaluation of the look content curriculum implementation program includes implementation, organization, teaching staff, students, funding budget, facilities and infrastructure, and evaluation of learning outcomes. The results of the study show that the entire program for implementing the local content curriculum can run well, although there are still many shortcomings that still need to be addressed. Thus the development of a local content curriculum can have a positive impact on other Islamic boarding schools in the Banyumas district. ABSTRAKTujuan penelitian ini untuk mengetahui pengembangan kurikulum muatan lokal di pondok pesantren modern Al-Azhary Lesmana Ajibarang Banyumas. Penelitian ini merupakan penelitian kualitatif menggunakan evaluasi kesenjangan (DEM). Penelitian ini dilakukan pada awal tahun 2022. Pengumpulan data menggunakan observasi, wawancara, dan dokumantasi. Data dianalisis secara deskriptif kualitatif. Evaluasi program pelaksanaan kurikulum muatan lokal mencakup pelaksanaan, pengorganisasian, tenaga guru, siswa, anggaran pembiayaan, sarana prasarana, dan evaluasi hasil pembelajaran. Hasil penelitian menunjukan keseluruhan program pelaksanaan kurikulum muatan lokal dapat berjalan dengan baik, meskipun masih banyak kekurangan yang masih perlu dibenahi. Dengan demikian pengembangan kurikulum muatan lokal dapat memberikan dampak positif dalam pembelajaran sekolah modern (pondok pesantren) Al-Azhary Ajibrang Banyumas. Kata kunci: Manajemen, Pengembangan Kurikulum, Muatan Lokal